Hubungan Pemberian ASI Eksklusif dengan Tumbuhnya Gigi Sulung Pada Bayi Usia 6-36 Bulan di Posyandu Wilayah Kerja Puskesmas Tanah Garam - Avilia Chandrawita; Kuswardani Susari P; Hidayati Hidayati (Andalas Dental Journal, 2019)
Background of the study: Exclusive breastfeeding is only receives breastmilk without any addition of other liquids or foods before reaching 6 months of age, where exclusive breastfeeding is the best source of nutrition and contains important nutrients that affect on the growth and the development of teeth eruption in infants. Objective: This study intended to find out the relationship of giving exclusive breastfeeding with the eruption of deciduous teeth in infants age 6-36 months at Integrated Service Post (Posyandu) in the working area of Tanah Garam Community Health Center. Method: This study used observational anaysis method with cross-sectional design. The sample taken by using Random Sampling technique in infants age 6-36 months at Integrated Service Post (Posyandu) in the working area of Tanah Garam Community Health Center as many as 95 infants. Data retrieval was carried out by interview using a questionnaire and then performed dental eruption examination. Data analysis used Chi-Square test. Result: The result of univariate analysis obtained that most of infants age6-36 months at Integrated Service Post (Posyandu) in the working area of Tanah Garam Community Health Center receive exclusive breastmilk and timing of teeth eruption on time. The result of bivariate analysis obtained p value < 0,05. Conclusion: There is significant relationship between the giving of exclusive breastfeeding with the eruption of deciduous teeth in infants age 6-36 months at Integrated Service Post (Posyandu) in the working area of Tanah Garam Community Health Center.